1976
DOI: 10.1007/bf00344793
|View full text |Cite
|
Sign up to set email alerts
|

The physiological ecology of Mytilus californianus Conrad

Abstract: The rates of oxygen consumption, filtration and ammonia excretion by Mytilus californianus have been related to body size and to ration. The rate of oxygen consumption (VO) by individuals while immersed, measured on the shore, resembled rates recorded for mussels starved in the laboratory. VO by M. californianus was relatively independent of change in temperature, with a Q (13-22° C) of 1.20. In contrast, the frequency of heart beat was more completely temperature dependent [Q (13-22° C)=2.10]. Filtration rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(96 citation statements)
references
References 28 publications
7
86
0
1
Order By: Relevance
“…Gills are the principal site of gas exchange and, thus, are likely poised to cope with fluctuating environmental oxygen concentrations and/or with variation in ROS production driven by changes in body temperature. Mantle tissue may assume some of this gasexchange function when the animal is emersed [59]; mantle had the highest levels of antioxidant capacity against peroxyl radicals. Muscle, on the other hand, is generally considered to function largely via anaerobic pathways [59].…”
Section: (B) Antioxidant Capacities Of All Tissues Respond To Environmentioning
confidence: 99%
See 1 more Smart Citation
“…Gills are the principal site of gas exchange and, thus, are likely poised to cope with fluctuating environmental oxygen concentrations and/or with variation in ROS production driven by changes in body temperature. Mantle tissue may assume some of this gasexchange function when the animal is emersed [59]; mantle had the highest levels of antioxidant capacity against peroxyl radicals. Muscle, on the other hand, is generally considered to function largely via anaerobic pathways [59].…”
Section: (B) Antioxidant Capacities Of All Tissues Respond To Environmentioning
confidence: 99%
“…Mantle tissue may assume some of this gasexchange function when the animal is emersed [59]; mantle had the highest levels of antioxidant capacity against peroxyl radicals. Muscle, on the other hand, is generally considered to function largely via anaerobic pathways [59]. While muscle rspb.royalsocietypublishing.org Proc.…”
Section: (B) Antioxidant Capacities Of All Tissues Respond To Environmentioning
confidence: 99%
“…2) it follows that the ammonia-N production was inversely related to the quantity of food consumed, as shown in Figure 3. Little data exists on the influence of nutritional levels on the rate of ammonia excretion for bivalve molluscs, except for starved animals (Bayne, 1973(Bayne, , 1976Bayne et al, 1976). However, the effects of nutrition have been more thoroughly investigated for zooplankton where it has usually been found that nitrogen excretion increases with an increased ration (Corner et al, 1965;Butler et al, 1970;Takahashi & Ikeda, 1975).…”
Section: Ammonia Production By Tapes Japonicamentioning
confidence: 99%
“…One other possibility has to be considered before we may conclude that nutritional levels are or are not inversely related to ammonia-N excretion for T. japonica. Bivalves will normally satisfy their metabolic energy requirements by using carbohydrates, then lipids and then protein (Gabbott & Bayne, 1973;Bayne, 1976). So, it is possible that at the lower food levels the protein in the phytoplankton would be utilized for the metabolic requirements and that the resulting deamination of the protein would increase the rate of ammonia excretion at the lower food levels.…”
Section: Ammonia Production By Tapes Japonicamentioning
confidence: 99%
“…When we independently estimated the contribution of mussel excretion, the estimates were concordant with our tidepool tracer dilution calculations. We used an empirically derived relationship between NH z 4 production and mussel dry mass (dry mass, g); NH z 4 production (mg h 21 ) 5 23.88 dry mass 0.817 (Bayne et al 1976a) derived from Northern Puget Sound where summer water temperatures and salinities are similar to those in the Strait of Juan de Fuca. Using our prior measurements of shell length and abundance in each experimental tidepool and the relationship between mussel dry mass and shell length (J. T. Wootton pers.…”
mentioning
confidence: 99%